USO DE RIZOBACTÉRIAS PARA AMENIZAR OS EFEITOS DELETÉRIOS DO DÉFICIT HÍDRICO NAS CULTURAS DE SOJA E FEIJÃO - ZOZ, Jardel; Zuffo, Alan Mario; Silva, Elijanara Raissa; Steiner, Fábio (ANAIS DO ENIC, 2018)
-